The Positioning of India in the U.S. Indo-Pacific Strategy Based on Alliance Theory (Journal of Interdisciplinary Insights, 2024)
This study explores India's positioning in the U.S. Indo-Pacific Strategy within the framework of Alliance Theory. It analyzes the strategic convergence between the U.S. and India, particularly in countering the rise of China, highlighting the evolution of the U.S.-India partnership as a critical element of the Indo-Pacific security architecture. The research addresses challenges faced by this partnership, including differences in geopolitical priorities and India's pursuit of strategic autonomy. Additionally, it examines the role of multilateral mechanisms such as the Quadrilateral Security Dialogue (Quad) and AUKUS, illustrating how India utilizes its "quasi-ally" status to enhance its influence while balancing relationships with both the U.S. and China. These findings contribute to a deeper understanding of the strategic dynamics between the U.S. and India and their implications for regional security in the Indo-Pacific.
Keywords: Indo-Pacific Strategy; Alliance Theory; U.S.-India Partnership; China; Strategic Autonomy